2020
DOI: 10.1111/jam.14806
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variability of human and fish viruses in mussels inside and offshore of Ravenna’s harbour (Adriatic Sea, Italy)

Abstract: Aims This study aims to investigate the presence and spatial‐seasonal variability of human and fish viruses in coastal marine systems using Ravenna’s harbour area (Adriatic Sea, Italy) as a model. Methods and Results Human viruses (noroviruses and hepatitis A virus) and one of the most threatening finfish pathogens, the nervous necrosis virus (NNV), were investigated in mussels living inside and offshore Ravenna’s harbour. Thirty‐three and 36·7% of tested mussel samples resulted contaminated by human and fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
2
15
2
Order By: Relevance
“…To date, the SJNNV/RGNNV reassortant has been mainly identified in fish species from Italy or Greece [35,36]. Interestingly, the reassortant SJNNV/RGNNV has been recently detected in mussels collected in the Adriatic Sea [9]. The RGNNV/SJNNV reassortants exhibit a slightly modified SJNNV capsid protein [4], thus, we can assure that this reassortant was not detected in the present study.…”
Section: Detection Of Rgnnv In Squid and Shrimp Species Collected In ...mentioning
confidence: 58%
See 4 more Smart Citations
“…To date, the SJNNV/RGNNV reassortant has been mainly identified in fish species from Italy or Greece [35,36]. Interestingly, the reassortant SJNNV/RGNNV has been recently detected in mussels collected in the Adriatic Sea [9]. The RGNNV/SJNNV reassortants exhibit a slightly modified SJNNV capsid protein [4], thus, we can assure that this reassortant was not detected in the present study.…”
Section: Detection Of Rgnnv In Squid and Shrimp Species Collected In ...mentioning
confidence: 58%
“…Regarding the Mediterranean sea, RGNNV has been detected in bivalve mollusks in the coast of Italy [20], in the Adriatic Sea [21] and in Greece [22]. A recent study on bivalve mollusks in the Adriatic Sea reported apparent RGNNV/SJNNV reassortants, although RGNNV was the main strain detected [9]. As for other invertebrate species, NNV was also documented in Italy in naturally deceased specimens of cultured and wild octopus presenting skin lesions [23], in Greece in gastropod samples [22] and in specimens of the blue crab from the Levantine Sea [24].…”
Section: Of 14mentioning
confidence: 99%
See 3 more Smart Citations